Brothers in Brackets? A Plea for Rethinking the Use of [] in NA/UBS - Aasgaard, Reidar (Journal for the study of the New Testament, 2004)
In their common main text, the last three editions of the Nestle-Aland Novum Testamentum Graece (NA) and the United Bible Societies’ Greek New Testaments (UBS) follow the long-established tradition of putting material of problematic authenticity within square brackets. Although there has over time taken place a development in these two publications towards a more positive assessment of the bracketed material, this has so far had no consequences with regard to their actual practice of bracketing. This article makes a sample inquiry into the authentic Pauline letters, viz. of some bracketed instances of address in the imperative ([ILLEGIBLE]). On the basis of external and internal criteria, and of the general tendency in important early manuscripts to omit certain types of material, it is argued that there are good reasons for reassessing the attitude and practice of bracketing in NA/UBS, preferably in order to reduce the amount of material in brackets.